Educação, protestantismo e sociedade: um estudo sobre o seminário teológico de São Paulo - Lopes, Leandro de Proença (2013)
The aim of this thesis is to analyze the relations between Protestantism and Education in Brazil, carrying out this objective through a research on School Institutions History. The studied institution is the Theological Seminary of São Paulo, raised by the Independent Presbyterian Church of Brazil to promote the theological education and to graduate the protestant priesthood to arrange its board, enabling itself to achieve its space in the city which had already presented features of the development that would change it on the economic field of the country. Supported in the principle protestant concepts of Paul Tillich, we have tried to identify if the studied institution has defined as educative project the formation of protestant spirit in its students, to know, the critical perception which has the objective of changing the society therewith the protestant ideals. We have established a relation with the thoughts of Antonio Gramsci about the intellectuals and the formation of culture; the author distinguishes the intellectuals in traditional and organic, defending that only the second kind has a critical posture. Thus, to verify if the protestant principle is present on the educative project of the referred institution, it has been questioned if the theologian, graded there, can be characterized as an organic intellectual. From this problematic render it has been done a historical research, underlay on the conjecture of the professor Ester Buffa that research a school institution is a way of studying the philosophy and history of the Brazilian education . Making use of the theoretical sidelights of the first generation of the Annales School, Lucien Febvre and Marc Bloch, to guide the historical research. Set up on April 21st, 1905, the Theological Seminary of São Paulo remained most of its history running as a free course, acquiring acknowledgment from MEC in 2012. Its history has been marked by conflicts of opposed educative projects, synthesized in expressions: graduate to the church or to the world. There hasn t been predominance of only one project. Despite this, verifying the path of the egresses, there have been verified that a considerable number wouldn t restrict them on church acting, but on searching other areas to exercise their vocation, predominating in teaching, what has allowed to conclude that protestant theological education has the vocation of forming the organic intellectual to be a critical of the inserted society.